Religious Tourism in Nyatnyono Village Semarang - Hendri Hermawan Adinugraha; Mila Sartika; Wikan Isthika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2018)
The purpose of this study was to describe the potential and reality of religious tourism in Nyatnyono Village. This research is a type of field research with descriptive analyticalapproach. The results of this study was indicated that in addition to potential religious tourism, Nyatnyono Village also has other tourism potential. The development of the potential of Nyatnyono Village as a natural tourism, educational tourism, and cultural tourism which has been foundin Dusun Ngaglik, DusunGelap, DusunSipol, DusunKrajan and DusunSiroto (top of Nyatnyono Village). While the potential of Nyatnyono Village as industrial tourism and educational tourism has been located in DusunSendang Putri, DusunSendang Rejo and DusunBlanten (bottom of Nyatnyono Village). Implementation of tourism potential information in Nyatnyono Village can be carried out if it receives support from the village government through Village Owned Enterprises (BUMDES), Tourism Awareness Groups (POKDARWIS) and local community. The development of tourism diversification in Nyatnyono Village will have an impact on other sectors such as the environment, social and economy. With the development of tourism, it will automatically open opportunities for local community to open goods or services businesses related to the facilitation of visitors. This will directly affect local employment, reduce unemployment and increase income.